If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2p + 5 = 5p + 2 Reorder the terms: 5 + 2p = 5p + 2 Reorder the terms: 5 + 2p = 2 + 5p Solving 5 + 2p = 2 + 5p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-5p' to each side of the equation. 5 + 2p + -5p = 2 + 5p + -5p Combine like terms: 2p + -5p = -3p 5 + -3p = 2 + 5p + -5p Combine like terms: 5p + -5p = 0 5 + -3p = 2 + 0 5 + -3p = 2 Add '-5' to each side of the equation. 5 + -5 + -3p = 2 + -5 Combine like terms: 5 + -5 = 0 0 + -3p = 2 + -5 -3p = 2 + -5 Combine like terms: 2 + -5 = -3 -3p = -3 Divide each side by '-3'. p = 1 Simplifying p = 1
| 36=2(3[w*2])+2w | | 2x^2+16x=5 | | 0.027m+2=0.035m+0 | | (12x^2)+7x-45=0 | | 3y(x^2+12-29)= | | X^4=15 | | .3x=2(3x+9) | | 16=1.8c+32 | | 5x^2-60x+10=0 | | 0.027+2=0.035+0 | | 12d-8=8d-5 | | 117-5x=40x+17 | | 3b-5=10 | | 3x^2+15x-30=0 | | 4.2(y-2)=2x-4 | | 23y-4=22y+8 | | x^2-9x=8 | | 6+11=46-4 | | 3(2a-5)= | | 5x+14=-28-9x | | x(9x-5)=14 | | 3(5b+4)= | | 4x^3-14x^2+6x=0 | | 6v+8v=-11-8 | | 3x-2=4x-9 | | 5w-2w=-5-4 | | -28=4w | | x-2+3x=-12+x-8 | | 3(n-2)=12 | | 4(x-5)-5=6x+33 | | 10+2(3+2x)=0 | | 3(x+5)+5(2x+10)= |